Data from the Race Implicit Association Test on the Project Implicit Demo Website. Issue 1 (18th March 2014) - Xu, Kaiyuan; Nosek, Brian; Greenwald, Anthony G.
This data archive includes Race Implicit Association Test (IAT) scores of 2, 355, 303 Internet volunteers who completed educational/demonstration versions of the Race IAT athttps://implicit.harvard.edu from 2002 to 2012. Data in this archive can be downloaded for all years, either separately by year or in a single file. Codebooks, indicating the variable labels and value labels, and changes of variables over years, are available for both individual-year data sets and the entire data set. Participation in the (still on-going) Race IAT "study" at the Project Implicit (PI) demonstration site includes completion of the Race IAT along with demographic questions, self-report measures of racial attitude, and various additional measures received by a portion of the participants. These data allow analyses involving changes in responding over time and interrelations among IAT and self-report measures of race attitudes, as well as the association of each of these with demographics. This archive is available athttp://osf.io/project/52qxL/ . Dataset: The Data described in this paper is available from the Open Science Framework:https://osf.io/52qxl/ [1 ].